12/15-Lipoxygenase Is an Interleukin-13 and Interferon-γ Counterregulated-Mediator of Allergic Airway Inflammation. (29th September 2010) - Lindley, Alexa R.; Crapster-Pregont, Margaret; Liu, Yanjun; Kuperman, Douglas A.
Abstract : Interleukin-13 and interferon-γ are important effectors of T-helper cells. Interleukin-13 increases expression of the arachidonic acid-metabolizing enzyme, 15-lipoxygenase-1, in a variety of cell types. 15-lipoxygenase-1 is dramatically elevated in the airways of subjects with asthma. Studies in animals indicate that 15-lipoxygenase-1 contributes to the development of allergic airway inflammation but is protective in some other forms of inflammation. We tested the hypothesis that the ability of interleukin-13 and interferon-γ to counterregulate allergic airway inflammation was potentially mediated by counterregulation of 12/15-lipoxygenase, the mouse ortholog of 15-lipoxygenase-1. The airways of mice were treated with interleukin-13 or interferon-γ one day prior to each of the four allergen exposures. Interleukin-13 augmented and interferon-γ inhibited allergic airway inflammation independently of systemic IgE and mucosal IgA responses but in association with counterregulation of 12/15-lipoxygenase. Interleukin-13 and interferon-γ counterregulate 12/15-lipoxygenase potentially contributing to the effects of these cytokines on allergic airway inflammation.